Performance Evaluation of 3Φ Asymmetrical MLI with Reduced Switch Count - Chinnapettai Ramalingam Balamurugan; S.P. Natarajan; T.S. Anandhi (Indonesian Journal of Electrical Engineering and Computer Science, 2016)
The multi level inverter system is habitually exploited in AC drives, when both reduced harmonic contents and high power are required. In this paper, a new topology for three phase asymmetrical multilevel inverter employing reduced number of switches is introduced. With less number of switches, the cost, space and weight of the circuit are automatically reduced. This paper discusses the new topology, the switching strategies and the operational principles of the chosen inverter. Simulation is carried out using MATLAB-SIMULINK. Various conventional PWM techniques that are appropriate to the chosen circuit such as PDPWM, PODPWM, APODPWM, VFPWM and COPWM are employed in this work. COPWM technique affords the less THD value and also affords a higher fundamental RMS output voltage.